Can Ego Depletion and Post-event Discussion Change the Way We Remember a Crime? - Harkness, E.; Paterson, H.; Denson, T.; Kemp, R.; Mullan, Barbara; Sainsbury, K. (2015)
© 2014 The Australian and New Zealand Association of Psychiatry, Psychology and Law. Ego depletion refers to a state of temporarily reduced self-regulatory capacity. Regulating emotional and cognitive responses to witnessing a violent or distressing event likely induces ego depletion. The current study investigated whether experimentally induced ego depletion would increase susceptibility to memory conformity. Participants viewed a mock crime video and then engaged in a depleting task or a non-depleting control task, before either discussing the video with a confederate who introduced accurate and misleading information or engaging in an individual recall task. Replicating the memory conformity effect, engaging in a post-event discussion reinforced memory for both accurate and misleading information. However, when depleted participants engaged in post-event discussion, they recalled less of the accurate (but the same amount of misleading) post-event information than non-depleted participants. This research suggests that depleted witnesses may suffer the negative consequences of discussion (remembering incorrect post-event information) without the possible benefit of remembering correct information.